An Overview of People, Process, and Physical Evidence at BPK Penabur High School Bogor - Charisa, Lisa; Fadillah, Adil (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Business development in Indonesia today has experienced significant progress and improvement compared to before. The Indonesian economy has moved towards the service sector. Based on data from the Institute for Development of Finance and Economics, Indonesia has moved toward the service industry. The service industry is an activity that service providers offer to consumers as a service that cannot be seen, felt, heard, or touched, but can be felt by consumers. The education business is one of the most sustainable businesses because of the need for parents to provide good education and the needs of children is increasing from time to time along with the advancement of a country's economy. BPK Penabur Bogor is a Christian Education Community named Badan Pendidikan Kristen (BPK) PENABUR Foundation. This educational foundation was established on 19 July 1950 in Bandung and is under the auspices of the Indonesian Christian Church Synod of West Java Region. Until now, BPK PENABUR has established 164 schools spread across 15 cities in 4 provinces (namely) West Java, DKI Jakarta, Banten 4 and Lampung. Based on the chart above, BPK Penabur High School has 30 schools spread across many cities and provinces. Jakarta has the most high schools, which is 8 schools. BPK Penabur High School Bogor uses People, Process, and Physical Evidence in its marketing. For example, it implements a recruiting system, provides training, rewards, and opportunities for employee communication. BPK Penabur High School Bogor has the biggest advantage in terms of physical evidence that is supportive structures and infrastructure that is used for marketing.